Modeling the activities of small enterprises located in the russian regions - Pinkovetskaia, Iuliia; Kryukova, Lyudmila (Revista de la Universidad del Zulia, 2019)
The aim of the study was to assess the two-factor production function describing the dependence of the turnover of small enterprises in the regions on the wages of workers and investments in fixed assets. The study was based on the empirical spatial data characterizing the activities of small enterprises, including microenterprises. We used the official statistical information on 82 Russian regions in 2017. The study made it possible to prove the high quality of the approximation of the initial data obtained by the two-factor production function. The results of the study, namely, new knowledge for evaluating the production activities of small enterprises, have scientific and practical significance. They can be used in new science research, monitoring the entrepreneurial climate, determining resource requirements, justifying small business development plans and programs.